Análise de dados aplicada às Cidades Inteligentes: reflexões sobre a Região Nordeste do Brasil - Jane Roberta de Assis Barbosa; Ignacio Sánchez-Gendriz (Confins)
Smart cities, as a bet for urban management purposes, have attracted the attention of researchers and public managers around the world. In 2020, 36 municipalities are categorized as “smart cities”, in the Brazil’s Nordeste. This article describes the methods used to analyze, visualize, and discuss some variables related to these 36 cities. From a spatial perspective, the use of thematic maps allowed to evince some characteristics of these municipalities. The association of thematic maps with data mining methods and a critical theoretical perspective proved to be useful to understand the territorial dynamics of smart cities. By combining the variables from the studied cities, principal component analysis and hierarchical clustering automatically identified similarities and differences between them. In comparison with the metropolises and capitals included in this study, cities with the conditions to better promote and/or harbor territorial dynamics characteristic of smart cities are: Jaboatão dos Guararapes-PE, Olinda-PE, Igarassu-PE, São Lourenço da Mata-PE, Moreno-PE, Itapissuma-PE, which are part of the Metropolitan Region of Recife; and Parnamirim-RN from the Metropolitan Region of Natal.